A minimum income standard for the UK in 2013 - Donald Hirsch (2013)
This is the 2013 update of the Minimum Income Standard (MIS) for the United Kingdom, based on what members of the public think people need for an acceptable minimum standard of living. This update in minimum budgets is based on increases in living costs. The findings also reflect changes in the tax and benefits systems, which affect both people’s living standards and the earnings required to reach a minimum net income. The report describes the ways in which people on lower incomes are being squeezed by a combination of sluggish income growth, restrictions on increases in benefits and tax credits, and rising living costs. It also notes the extent to which increases in income tax allowances help to alleviate this squeeze. This report shows: • what incomes different family types require in 2013 to meet the minimum standard; and • how much the cost of a minimum household budget has risen since the last update in 2012.